Bionic flutter wing piezoelectric-electromagnetic composite energy harvesting system. (1st November 2022) - Bo, Fan; Jiwen, Fang; Jiuchun, Zhao; Chong, Li; Jia, Wang; Mingming, Lv
Highlights: A composite energy harvesting system based on dipteran insects is proposed. Piezo-bionic flapping-wing flexible beam harvests vibration energy. One excitation source for simultaneous piezoelectric and electromagnetic conversions. High-performance energy harvesting at ultra-low frequencies below 5 HZ. The compound energy harvesting power up to 69.14 MW. Abstract: The bionic structure has great potential in the field of energy harvesting. Inspired by the fluttering structure of dipteran insects, this paper proposes a novel bionic multi-domain energy harvester based on the mechanism of fluttering behavior of dipteran insects. The device is designed concerning the skeletal and muscular structures of dipteran insects, using a flexible cantilever beam and a rigid linkage to simulate the fluttering wings and skeletal structures of dipteran insects, while the reciprocating motion generated by the central permanent magnet with the cooperation of gravity and a limiting spring simulates the muscle contraction of dipteran insects. In the process of simulating the fluttering motion, the piezoelectric sheet installed on the cantilever beam can harvest the vibration energy, while the magnetic induction coil arranged on the outside of the central permanent magnet can harvest the electromagnetic energy generated by the vertical reciprocating motion, providing a second channel of energy harvesting for the bionic fluttering wing piezoelectric-electromagnetic composite energy harvesting (BCEH) system. Based on the electromechanical coupling characteristics of the energy harvesting device, a centralized parametric dynamics model of the system is established. The modal analysis of the bionic structure is carried out by using the finite element method, and the natural frequency and mode shape of the structure are determined. The key structural parameters are optimized through theoretical calculation and simulation. After optimization, the output voltage and output power of the proposed energy harvester have been effectively improved. The output voltage of the piezoelectric port has been increased by up to 347%, and the output power has been increased by up to 1789%. The output voltage of the electromagnetic port has been increased by up to 40%. The output power has been increased by up to 137%. So the experimental results show that the bionic flapping-wing composite energy harvesting system can achieve better energy harvesting.